Method for producing rolled surface-treated steel sheet, and rolled surface-treated steel sheet

By forming an iron-nickel alloy layer on the steel plate and carrying out specific rolling processes, the problem of cracking of nickel-plated steel foil during charging and discharging is solved, and the foil is improved through plateability and crack resistance is ensured that the foil is not easy in the production line Scratched.

CN119452122APending Publication Date: 2025-02-14TOYO KOHAN CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380049697.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2023-04-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the charging and discharging process of the current collector of the secondary battery, the coating of the nickel-plated steel foil cracks due to elongation, resulting in the exposure of the iron of the substrate, and then dissolution in the alkaline electrolyte, causing the foil surface to be scratched in the production line hurt.

Method used

The iron-nickel alloy layer is formed on the steel plate, and after the layer is formed, it is rolled at a depressing rate of 5 to 25%, so as to control the grain orientation and grain size of the iron-nickel alloy layer, and improve the plateability and resistance of the foil Cracking.

Benefits of technology

By maintaining the hardness of the surface and suppressing the occurrence of cracking, the through-plate properties and crack resistance of the rolled surface-treated steel plate are improved, ensuring that the foil is not easily scratched when passing through the production line.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452122A_ABST
    Figure CN119452122A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of maintaining the hardness of the surface of a rolled surface-treated steel sheet, suppressing the occurrence of cracks even in a state in which elongation is imparted, and improving plate passing properties when passing between a drawing roll and a plate passing roll. A method for manufacturing a rolled surface-treated steel sheet, the method comprising: an iron-nickel alloy layer formation step for forming an iron-nickel alloy layer on a steel sheet as a base material; and a rolling step in which, after the iron-nickel alloy layer formation step, the steel sheet having the iron-nickel alloy layer is rolled at a reduction rate of 5-25%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a rolled surface-treated steel plate and the rolled surface-treated steel plate. Background Art

[0002] Nickel-plated steel foil is known as a raw material for components constituting batteries and components constituting electronic related devices. In such nickel-plated steel foil, for reasons such as improving corrosion resistance with a small amount of nickel, the following method is adopted: a diffusion alloy layer containing nickel and iron is formed on a steel plate, and the nickel-plated steel plate is cold-rolled at a high reduction rate to obtain the nickel-plated steel foil for the purpose of controlling the structure of the diffusion alloy layer.

[0003] Patent document 1 discloses the following method for manufacturing steel foil: a steel sheet having a nickel plating layer is annealed to allow the Ni in the plating layer and the Fe in the steel sheet to diffuse mutually, and then cold-rolled under conditions of a cumulative reduction rate of 70% or more, thereby forming a specific aggregate structure on the surface layer while making the thickness less than 100 μm.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2013 / 157600 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The steel foil obtained by the conventional manufacturing method has the following problems, not limited to the above manufacturing method. That is, when the collector of the secondary battery is repeatedly subjected to elongation during charging and discharging, the plated layer is cracked due to the elongation, and the iron as the base material is exposed, which may be dissolved in a highly corrosive electrolyte such as an alkaline electrolyte. Furthermore, when assembling secondary batteries and electronic related equipment, the foil is passed through the plate rollers many times in the production line, but it is desired to make the steel foil without scratches on the foil surface at this time.

[0009] The present invention has been made in view of solving such problems, and an object of the present invention is to provide a method for manufacturing a rolled surface-treated steel sheet that maintains surface hardness, suppresses cracking even when elongated, and improves sheet passability when passing between drawing rolls and sheet passing rolls.

[0010] Means for solving problems

[0011] In order to solve the above-mentioned problems, the manufacturing method of the rolled surface-treated steel plate in the present embodiment (1) comprises: an iron-nickel alloy layer forming process of forming an iron-nickel alloy layer on a steel plate serving as a substrate; and a rolling process of rolling the steel plate having the above-mentioned iron-nickel alloy layer at a reduction rate of 5 to 25% after the iron-nickel alloy layer forming process.

[0012] Among the above (1), preferably (2) the above-mentioned iron-nickel alloy layer forming process includes: a nickel plating process for forming a nickel plating layer on the above-mentioned steel plate serving as the substrate; and a heat treatment process for heat treating the nickel plating material obtained in the above-mentioned nickel plating process to form the above-mentioned iron-nickel alloy layer produced by diffusion.

[0013] Furthermore, in order to solve the above-mentioned problems, the rolled surface-treated steel plate in the present embodiment is characterized in that (3) it has a substrate composed of steel and an iron-nickel alloy layer arranged on the above-mentioned substrate, the above-mentioned iron-nickel alloy layer contains Fe1Ni1, and the orientation index of the (200) plane of Fe1Ni1 in the X-ray diffraction is greater than 0.7, and the orientation index of the (220) plane of the above-mentioned Fe1Ni1 in the X-ray diffraction is greater than 0.7 and less than 2.5.

[0014] In the above (3), preferably (4) the average crystal grain size of nickel measured by EBSD at the surface of the iron-nickel alloy layer is 0.4 μm to 1.1 μm.

[0015] In the above (3), preferably (5) the difference (absolute value) between the orientation index in X-ray diffraction of the (200) plane of the above Fe1Ni1 and the orientation index in X-ray diffraction of the above Fe1Ni1 (220) plane is 1.0 or less.

[0016] In the above (3), preferably (6) the orientation index of the (111) plane of the Fe1Ni1 in X-ray diffraction is 0.3 to 2.0.

[0017] Effects of the Invention

[0018] According to the present invention, it is possible to provide a method for producing a rolled surface-treated steel sheet in which the occurrence of cracks is suppressed even in a state where elongation is given while maintaining hardness and the passability of the steel sheet is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a flowchart which shows the manufacturing method of the rolled surface-treated steel sheet which concerns on this embodiment.

[0020] FIG. 2( a ) is a schematic diagram showing a method for measuring the hydrogen permeation current density of a rolled surface-treated steel sheet according to the present embodiment.

[0021] FIG. 2( b ) is a schematic diagram showing a method for measuring the hydrogen permeation current density of a rolled surface-treated steel sheet according to the present embodiment.

[0022] FIG. 2( c ) is a schematic diagram showing a method for measuring the hydrogen permeation current density of a rolled surface-treated steel sheet according to the present embodiment.

[0023] Figure 3 It is a schematic diagram showing a cross section of a rolled surface-treated steel sheet according to the present embodiment.

[0024] Figure 4 It is a schematic diagram showing a method of determining the thickness of the iron-nickel alloy layer included in the rolled surface-treated steel sheet according to the present embodiment.

[0025] Figure 5 It is a schematic diagram showing a cross section of a rolled surface-treated steel sheet in a modified example of the present embodiment. DETAILED DESCRIPTION

[0026] 《Method for manufacturing rolled surface treated steel plate》

[0027] The following describes an embodiment of a method for manufacturing a rolled surface treated steel sheet according to the present invention. The rolled surface treated steel sheet manufactured by the manufacturing method of this embodiment is used for collectors of positive or negative electrodes of secondary batteries, electronic related devices, and the like.

[0028] like Figure 1 As shown in, the manufacturing method of the rolled surface-treated steel plate of the present embodiment is characterized by comprising: an iron-nickel alloy layer forming process of forming an iron-nickel alloy layer on a steel plate (original plate) serving as a substrate; and a rolling process of rolling the steel plate having the above-mentioned iron-nickel alloy layer at a reduction rate of 5 to 25% after the above-mentioned iron-nickel alloy layer forming process.

[0029] <Preliminary process>

[0030] First, an original plate is prepared. The original plate referred to here is a steel portion that becomes a base material for forming an iron-nickel alloy layer in the iron-nickel alloy layer forming step described later. The original plate is preferably low-carbon steel or ultra-low-carbon steel.

[0031] As a specific example of the preliminary process, for a low-carbon hot-rolled steel sheet (hot coil) of about 2.0 mm to 3.0 mm, descaling is performed by a known pickling method. Next, after rolling with a reduction rate of more than 60% by a known cold rolling method to obtain a cold-rolled steel sheet of about 0.16 mm to 1.2 mm, a known continuous annealing is performed to remove the work hardening and soften it. Furthermore, by intermediate rolling, an original plate of the desired thickness can be obtained. It should be noted that the preliminary process for obtaining the original plate is not limited to the above.

[0032] The thickness of the original plate is in the range of 0.03 mm to 0.8 mm, and is not particularly limited. When a product having a thickness that is considered to be a "foil" is obtained after the rolling step described below, the thickness is preferably 30 μm to 190 μm.

[0033] Using the original plate obtained as described above, Figure 1 As shown in , an iron-nickel alloy layer is formed on an original plate (iron-nickel alloy layer forming process), and then the steel plate having the iron-nickel alloy layer is rolled at a reduction rate of 5 to 25% (rolling process), thereby manufacturing the rolled surface treated steel plate of this embodiment.

[0034] <Iron-nickel alloy layer forming process>

[0035] As the iron-nickel alloy layer forming process of this embodiment, there can be listed a method of forming a nickel plating layer on a steel plate serving as a substrate (nickel plating process), and then heat treating the nickel plating material obtained in the above-mentioned nickel plating process to form an iron-nickel alloy layer produced by diffusion (heat treatment process).

[0036] [An example of nickel plating bath (Watt bath) and plating conditions]

[0037] Bath composition:

[0038] Nickel sulfate hexahydrate: 200~300g / L

[0039] Nickel chloride hexahydrate: 20~60g / L

[0040] Boric acid: 10~50g / L

[0041] Bath temperature: 40~70℃

[0042] pH: 3.0~5.0

[0043] Stirring: air stirring or jet stirring

[0044] Current density: 5~30A / dm 2

[0045] In addition to the above-mentioned Watt bath, the known nickel sulfamate bath and citric acid bath can also be used for the bath composition. Furthermore, known additives such as brighteners can be added to the plating bath to form bright nickel plating or semi-bright nickel plating. In order to avoid hardening of the nickel film, matte nickel plating or semi-bright nickel plating without brighteners containing sulfur is preferred.

[0046] In the manufacturing method of this embodiment, the amount of nickel deposited in the nickel plating layer or the iron-nickel alloy plating layer formed on the steel sheet is preferably 0.89 g / m2 per single side from the viewpoint of cost and the electrolyte resistance of the obtained rolled surface-treated steel sheet. 2 ~28.1g / m 2, more preferably 0.93 g / m 2 ~26.7g / m 2 .

[0047] [Heat treatment process]

[0048] The heat treatment process in this embodiment is a process performed by heating the nickel layer formed on the original plate to diffuse the iron of the original plate and the nickel of the nickel layer to form an iron-nickel alloy layer generated by thermal diffusion. The heat treatment process in this embodiment can be continuous annealing or intermittent annealing (box annealing).

[0049] As an example of the temperature and time during the continuous annealing treatment, it is preferably carried out at 650°C to 950°C within a soaking time range of 15 seconds to 150 seconds. In the case of a lower temperature or a shorter time than this, it is possible that a sufficient iron-nickel alloy layer 30 cannot be obtained, which is not preferred. On the other hand, in the case of a higher temperature or a longer time than the above-mentioned heat treatment range, the mechanical properties of the steel foil or the like as the substrate change greatly, the strength is significantly reduced, or it is not preferred from the perspective of cost.

[0050] As an example of the temperature and time during intermittent annealing (box annealing), it is preferably carried out at 450°C to 690°C with a soaking time of 1.5 hours to 20 hours, and a total time of 4 hours to 80 hours for heating, soaking and cooling. In the case of a lower temperature or a shorter time than that, it is possible that a sufficient iron-nickel alloy layer 30 cannot be obtained, which is not preferred. On the other hand, in the case of a higher temperature or a longer time than the above-mentioned heat treatment range, the mechanical properties of the steel foil as a substrate change greatly, the strength may be significantly reduced, or it is not preferred from the perspective of cost.

[0051] <Rolling process>

[0052] Next, the rolling process in this embodiment is described. The rolling process in this embodiment is a process of cold rolling the steel plate formed with the iron-nickel alloy layer after the above-mentioned iron-nickel alloy layer forming process. The rolling process is aimed at obtaining the desired thickness of the rolled surface treated steel plate, controlling the metal crystals contained in the iron-nickel alloy layer to a preferred state, and improving the crack resistance and passability of the obtained rolled surface treated steel plate.

[0053] It is characterized in that the reduction ratio in the rolling process of the present embodiment is 5 to 25%. It is believed that by making the reduction ratio greater than 5%, it is possible to produce a state in which the orientations of the (200) plane and the (220) plane are appropriately mixed relative to the grains of the iron-nickel alloy (Fe1Ni1) contained in the iron-nickel alloy layer. Specifically, through the rolling process of the present embodiment, with regard to the orientation index in X-ray diffraction (XRD), it is preferred that the orientation index in the X-ray diffraction of the (200) plane of Fe1Ni1 (hereinafter also referred to as the orientation index of the (200) plane) is greater than 0.7 and the orientation index in the X-ray diffraction of the (220) plane of Fe1Ni1 (hereinafter also referred to as the orientation index of the (220) plane) is greater than 0.7 and less than 2.5. Furthermore, it is preferred that the difference (absolute value) between the orientation index in the X-ray diffraction of the (200) plane of Fe1Ni1 and the orientation index in the X-ray diffraction of the (220) plane of Fe1Ni1 be less than 1.0. It is considered that, in the rolling process of the present implementation process, by controlling the crystal state of the iron-nickel alloy as described above, the crack resistance can be improved while maintaining the appropriate hardness of the surface of the obtained rolled surface-treated steel plate.

[0054] On the other hand, from the viewpoint of crack resistance when elongation is imparted to the obtained rolled surface-treated steel sheet, the upper limit of the reduction ratio in the rolling step is preferably set to 25%.

[0055] In addition, the orientation index of the (200) plane of Fe1Ni1 in the X-ray diffraction and the orientation index of the (220) plane of Fe1Ni1 in the X-ray diffraction in this embodiment will be described later.

[0056] Furthermore, it is preferred that the rolling process of the present embodiment is such that the average grain diameter of nickel based on the electron beam backscatter diffraction (EBSD) measurement data is 0.4 μm to 1.1 μm. It should be noted that the average grain diameter obtained by the electron beam backscatter diffraction (EBSD) method can be obtained using a known measuring device and a measuring procedure. Specifically, the average grain diameter can be obtained by analyzing the information of a diffraction pattern called a Kikuchi pattern obtained under the following conditions. During the measurement, although the diffraction pattern of nickel is specified, information is obtained in the same diffraction pattern from an iron-nickel alloy having a face-centered cubic crystal structure close to nickel, so the average grain diameter of nickel using the EBSD measurement data in the present invention becomes the average grain diameter of nickel crystals, iron-nickel alloy crystals, or nickel crystals and iron-nickel alloy crystals.

[0057] <EBSD measurement conditions and analysis conditions>

[0058] ·SEM: SU8020 manufactured by Hitachi High-Tech

[0059] ·Measurement procedure: OIM Data Collection

[0060] Data analysis program: OIM Analys is (Ver.6.2.0)

[0061] ·Measurement range: 100μm×120μm

[0062] Grain Tolerance Angle: 5°

[0063] Step width: 0.20μm

[0064] Average (diameter)

[0065] It is believed that the rolling process of the present embodiment is performed by rolling at a reduction rate of 5 to 25% after the iron-nickel alloy layer is formed, so that the orientation of both the (200) plane and the (220) plane is appropriately present for the crystal orientation of the nickel alloy, and processing strain is applied at the same time, so that the average grain size of the nickel measured by the EBSD data can be controlled within the range of 0.4 μm to 1.1 μm as described above. It is believed that by making the average grain size within this range, the increase in the friction coefficient of the surface of the obtained rolled surface treated steel plate can be suppressed. In addition, it is believed that the hardness of the outermost surface of the obtained rolled surface treated steel plate and the intermediate layer between the substrate and the outermost surface can be within an appropriate range.

[0066] The rollers that play a role in the rolling process of the present embodiment may be one group or multiple groups. Usually, the rolling mill is composed of a plurality of combinations of upper and lower rollers that directly act to thin the plate, that is, rollers and rollers for passing the plate. During rolling, sometimes the rollers that play a role in rolling are one group, and sometimes multiple rollers play a role. In the present embodiment, the rollers that play a role in the rolling process may be one group or multiple groups. In addition, for example, three groups of rollers can pass the plate twice and a total of six groups of rollers can be used for rolling. Generally, if the number of times the rollers are passed increases, it is easy to produce adverse situations caused by work hardening during rolling. Therefore, the rollers that play a role in rolling are preferably less than 6 groups, more preferably less than 3 groups, and can be 2 groups or 1 group. It should be noted that here, the so-called one group of rollers is counted as the upper and lower rollers that are in direct contact with the plate and whose thickness changes before and after the rollers.

[0067] In addition, the above-mentioned reduction ratio refers to the reduction ratio obtained from the thickness of the plate before and after the rolling process. That is, when the plate is passed through three sets of rolls twice, it refers to the reduction ratio obtained from the thickness before the first pass and the thickness after the second pass.

[0068] In the rolling process, from the viewpoint of improving the crack resistance and sheet passing properties of the rolled surface treated steel foil, a rolling reduction rate of 10 to 20% is more preferred. The rolling reduction rate of the first set of rolls is not particularly limited.

[0069] After the rolling process, a rolled surface treated steel sheet can be obtained. The nickel adhesion amount of the obtained rolled surface treated steel sheet is preferably 0.89 g / m per single side. 2 ~26.7g / m 2 .

[0070] 《Rolled surface treated steel plate》

[0071] Hereinafter, the rolled surface-treated steel sheet in the present embodiment will be described. The rolled surface-treated steel sheet in the present embodiment is produced by the above-mentioned production method.

[0072] The rolled surface-treated steel sheet 1 of the present embodiment includes a base material 20 made of steel and an iron-nickel alloy layer 30 provided on the base material 20 .

[0073] <Base material 20>

[0074] As the base material 20 constituting the rolled surface treated steel sheet 1 of the present embodiment, a steel sheet based on iron containing less than 1.0 wt% of Cr and other added metal elements is preferred. Specifically, it is preferred to use low carbon steel (0.01 to 0.15 wt% carbon) represented by low carbon aluminum killed steel, ultra low carbon steel containing less than 0.01 wt% carbon, or non-aging ultra low carbon steel containing Ti, Nb, etc. added to the ultra low carbon steel.

[0075] The thickness of the substrate 20 constituting the rolled surface treated steel sheet 1 of the present embodiment is preferably in the range of 0.03 mm to 0.8 mm, more preferably 0.03 mm to 0.15 mm. The thickness of the substrate 20 is preferably measured by cross-sectional observation using an optical microscope or a scanning electron microscope (SEM).

[0076] <Iron-nickel alloy layer 30>

[0077] The iron-nickel alloy layer 30 contained in the rolled surface-treated steel plate 1 of the present embodiment is an alloy layer containing iron (Fe) and nickel (Ni), and is a metal layer containing an alloy composed of iron and nickel (also referred to as "iron-nickel alloy", "Fe-Ni alloy"). It should be noted that the alloy state composed of iron and nickel may be any of a solid solution, eutectoid / eutectic, and a compound (intermetallic compound), and they may also coexist.

[0078] As for the iron-nickel alloy layer 30 contained in the rolled surface treated steel plate 1 of the present embodiment, as long as the subject of the present invention can be solved, other metal elements and inevitable impurities may also be included. For example, in the iron-nickel alloy layer 30, metal elements such as cobalt (Co), molybdenum (Mo), and additive elements such as boron (B) may be included. It is to be noted that the proportion of metal elements other than iron (Fe) and nickel (Ni) in the iron-nickel alloy layer 30 is preferably less than 10 weight %, more preferably less than 5 weight %, and further preferably less than 1 weight %. The iron-nickel alloy layer 30 can be a binary alloy consisting essentially of only iron and nickel, so the lower limit of the proportion of other metal elements except the inevitable impurities is 0%.

[0079] The types and amounts of other metal elements contained can be measured by known means such as a fluorescent X-ray (XRF) measuring device and GDS (glow discharge luminescence surface analysis).

[0080] In the rolled surface treated steel sheet 1 in the present embodiment, it is characterized in that, in the above-mentioned iron-nickel alloy layer 30, while containing Fe1Ni1, the orientation index in the X-ray diffraction of the (200) plane of Fe1Ni1 is 0.7 or more, and the orientation index in the X-ray diffraction of the (220) plane of Fe1Ni1 is 0.7 or more and less than 2.5. Furthermore, it is preferred that the difference (absolute value) between the orientation index in the X-ray diffraction of the (200) plane of Fe1Ni1 and the orientation index in the X-ray diffraction of the (220) plane of Fe1Ni1 is 1.0 or less. It is to be noted that the above-mentioned orientation index can be achieved by applying rolling to the iron-nickel alloy layer 30. It is believed that: by the above-mentioned orientation index, the crack resistance and the passability can be improved while maintaining the appropriate hardness of the surface of the rolled surface treated steel sheet 1. In addition, it is believed that: by forming a random orientation in which the (200) plane and the (220) plane are appropriately mixed, the channel (path) of hydrogen between crystals can be extended, and the hydrogen barrier property is also excellent. From the viewpoint of maintaining appropriate hardness, improving crack resistance and sheet passability, the orientation index of the (220) plane is preferably greater than 0.7 and less than 2.0, and more preferably greater than 0.7 and less than 1.9. From the viewpoint of maintaining appropriate hardness, improving crack resistance and sheet passability, the upper limit of the (200) plane is preferably less than 2.0, and more preferably less than 1.7. In addition, from the viewpoint of obtaining more stable sheet passability, the difference (absolute value) between the orientation index of the (200) plane and the orientation index of the (220) plane is more preferably less than 0.8, and further preferably less than 0.7. The orientation index of the (200) plane and the orientation index of the (220) plane can be the same value, so the lower limit of their difference is 0.

[0081] The crystal orientation index Ico_Fe1Ni1(200) of the X-ray diffraction of the (200) plane of Fe1Ni1 and the crystal orientation index Ico_Fe1Ni1(220) of the X-ray diffraction of the (220) plane of Fe1Ni1 are calculated by the following definition: The subscript co means crystal orientation.

[0082] Ico_Fe1Ni1(200)=

[0083] [I_Fe1Ni1(200) / [I_Fe1Ni1(111)+I_Fe1Ni1(200)+I_Fe1Ni1(220)+I_Fe1Ni1(311)+I_Fe1Ni1(222)]]

[0084] / [I S _Fe1Ni1(200) / [I S _Fe1Ni1(111)+I S _Fe1Ni1(200)+I S _Fe1Ni1(220)+I S _Fe1Ni1(311)+I S _Fe1Ni1(222)]]

[0085] Ico_Fe1Ni1(220)=

[0086] [I_Fe1Ni1(220) / [I_Fe1Ni1(111)+I_Fe1Ni1(200)+I_Fe1Ni1(220)+I_Fe1Ni1(311)+I_Fe1Ni1(222)]]

[0087] / [I S _Fe1Ni1(220) / [I S _Fe1Ni1(111)+I S _Fe1Ni1(200)+I S _Fe1Ni1(220)+I S _Fe1Ni1(311)+I S _Fe1Ni1(222)]]

[0088] The diffraction intensity of each crystal plane of Fe1Ni1 measured by X-ray diffraction is expressed as follows.

[0089] I_Fe1Ni1(111): diffraction intensity of Fe1Ni1(111) crystal plane measured by X-ray diffraction

[0090] I_Fe1Ni1(200): diffraction intensity of Fe1Ni1(200) crystal plane measured by X-ray diffraction

[0091] I_Fe1Ni1(220): diffraction intensity of Fe1Ni1(220) crystal plane measured by X-ray diffraction

[0092] I_Fe1Ni1(311): diffraction intensity of Fe1Ni1(311) crystal plane measured by X-ray diffraction

[0093] I_Fe1Ni1(222): diffraction intensity of Fe1Ni1(222) crystal plane measured by X-ray diffraction

[0094] The diffraction intensity referred to here is the maximum value of the diffraction intensity (cps) measured in the range of ±0.11° for each diffraction angle (2θ) described in JCPDS (Joint Committee on Powder Diffraction Standards, PDF card number: 01-071-8322).

[0095] Specifically, the (111) plane is 43.83°±0.11°, the (200) plane is 51.05°±0.11°, the (220) plane is 75.10±0.11, the (311) plane is 91.23±0.11, and the (222) plane is the maximum value in the range of 96.56±0.11.

[0096] Furthermore, from the viewpoint of further improving crack resistance and plate passability, the iron-nickel alloy in the iron-nickel alloy layer 30 of the rolled surface-treated steel plate 1 in the present embodiment preferably has an orientation index of 0.3 to 2.0 on the Fe1Ni1(111) plane calculated in the same manner as above. Although the details are unclear, it is believed that the characteristics can be further improved by having a crystal orientation that is not biased towards the (111) plane in addition to the (200) plane and the (220) plane. More preferably, the orientation index of the Fe1Ni1(111) plane is 0.3 to 1.3. Furthermore, it is preferred that the orientation index of the Fe1Ni1(111) plane is 0.3 to 1.0 or the orientation index of the (111) plane is smaller than that of the (200) plane and the (220) plane.

[0097] Next, the method for evaluating hydrogen barrier properties is described. When hydrogen penetrates and moves in a rolled surface-treated steel plate, hydrogen atoms that reach the hydrogen detection side from the hydrogen intrusion side are oxidized to become hydrogen ions. The value of the oxidation current at this time increases or decreases according to the amount of hydrogen reaching the hydrogen detection surface, so the hydrogen barrier properties of the rolled surface-treated steel plate can be quantified and evaluated using the detected current value. (Miryu Tetsu, Tokyo Institute of Technology, Materials and Environment, 63, 3-9 (2014), Measurement of hydrogen intrusion and permeation into steel using electrochemical methods)

[0098] The inventors have measured and evaluated the above-mentioned expected results and have concluded that in order to suppress the occurrence of the above-mentioned voltage drop (self-discharge), the hydrogen permeation current density obtained from the oxidation current value measured by electrochemical measurement is preferably 10 μA / cm 2 The following is an explanation of the measurement conditions of the hydrogen permeation current density in the present embodiment, which are as follows: the liquid temperature of the electrolyte is 45°C, and the measurement area is φ60 mm in diameter (28.26 cm 2 ), a current of 2.25 A was applied to the hydrogen intrusion side, and no current was applied to the hydrogen detection side. The current value of 2.25 A on the hydrogen generation side is to generate a sufficient amount of hydrogen required for penetration and migration in the rolled surface treated steel plate.

[0099] As a specific example of the method for measuring the hydrogen permeation current density in the present embodiment, by using a measuring device having the structure shown in FIG. 2(a) to detect the current value (current density), the hydrogen barrier property of the rolled surface treated steel plate can be quantified and evaluated. The measuring device shown in FIG. 2(a) is described below. In the following description, the hydrogen intrusion side is also referred to as the hydrogen generation side, which is the side of the bipolar electrode structure where the hydrogen storage alloy is configured. In addition, the hydrogen detection side is the opposite side of the hydrogen intrusion side, which is the positive electrode side of the bipolar electrode structure.

[0100] Prepare two cells, cell X for hydrogen generation and cell Y for detecting hydrogen transmission, and set a test piece (sample) of a rolled surface treated steel plate between the two measuring cells. In each measuring cell, fill with an electrolyte (containing 6 mol / L of KOH as the main component, and the total concentration of KOH, NaOH, and LiOH is an alkaline aqueous solution with a concentration of 7 mol / L), and immerse the counter electrode (CE1 and CE2). For the counter electrode, platinum (Pt) is used. In addition, the temperature of the electrolyte is set to 45°C. In addition, as shown in Figure 2(b), the measurement diameter in the rolled surface treated steel plate is set to φ60mm (measurement area 28.26cm 2 ).

[0101] As for the current control on the hydrogen intrusion side, a rectifier is used as shown in FIG2(a). As the rectifier, for example, the "Small DC Stabilized Power Supply PMX18-5A" manufactured by Kikusui Electronics Industry Co., Ltd. can be used. In addition, as for the current measurement on the hydrogen detection side, an ammeter is used as shown in FIG2(a). As the ammeter, for example, the "Digital Marker DT4282" manufactured by Hioki Electric Co., Ltd. can be used. It should be noted that the sample of the rolled surface treated steel plate to be evaluated and the connection of each device can be carried out as shown in FIG2(a).

[0102] On the hydrogen generation side X, 2.25 mA is applied to the sample for 30 minutes to generate hydrogen on the sample surface and allow hydrogen to penetrate. It should be noted that on the hydrogen detection side Y, no potential is applied and only an ammeter is connected. In the case where hydrogen atoms penetrate from the hydrogen generation side, if the hydrogen atoms that penetrate are oxidized on the hydrogen detection side, the oxidation current measured by the ammeter on the hydrogen detection side changes (increases). Therefore, due to the change in oxidation current, it is possible to quantify and evaluate the hydrogen permeability of the rolled surface treated steel plate.

[0103] It should be noted that, before the current is applied on the hydrogen generating side, in order to stabilize the surface of the rolled surface treated steel plate, it is immersed in the electrolyte for more than 20 minutes, and the current value of the ammeter on the hydrogen detection side is confirmed to be less than 10μA and becomes stable. Through the above process, the minimum value of the oxidation current described later can be obtained. It should be noted that the measurement plot of the oxidation current value is set to be once every 10 seconds.

[0104] The hydrogen permeation current density I (μA / cm 2 Specifically, the difference between the oxidation current when the current was applied for 30 minutes and the current value immediately before the current was applied (0 seconds) was divided by the measurement area of ​​28.26 cm 2 The obtained value is the hydrogen permeation current density. 2 ) is shown in Figure 2(c).

[0105] In this embodiment, the following conclusions were obtained: using the apparatus shown in FIG. 2 , in the above electrolyte at 45° C., the hydrogen permeation current density on the hydrogen detection side when measured under the condition that the current value on the hydrogen intrusion side was 2.25 A was 10 μA / cm 2 In the case below, from the viewpoint of hydrogen barrier property in the rolled surface treated steel sheet, a bipolar electrode is preferred. From the viewpoint of further suppressing voltage drop, 2.5 μA / cm 2 Below, more preferably 2.0 μA / cm 2 Below, particularly preferably less than 1.0 μA / cm 2 .

[0106] Furthermore, on the surface of the iron-nickel alloy layer 30 of the rolled surface-treated steel plate 1 in the present embodiment, it is preferred that the average grain diameter of nickel measured by the electron beam backscatter diffraction method (EBSD) is 0.4 μm to 1.1 μm. It should be noted that the above-mentioned average grain diameter can be achieved by rolling the iron-nickel alloy layer 30. It should be noted that the average grain diameter obtained by the electron beam backscatter diffraction method (EBSD) can be obtained by using known measuring equipment and measuring procedures as described above. It is believed that by controlling the above-mentioned average grain diameter, the increase in the friction coefficient of the surface of the rolled surface-treated steel plate 1 can be suppressed. In addition, it is believed that the hardness of the outermost surface of the rolled surface-treated steel plate 1 and the intermediate layer between the substrate and the outermost surface can be brought into an appropriate range.

[0107] Regarding the surface hardness of the rolled surface treated steel sheet 1 in the present embodiment, from the viewpoint of crack resistance and scratch resistance, the hardness at a depth of 0 to 2.2 μm from the surface when measured using a micro Vickers hardness tester with a load of 10 g is preferably 120 to 230. It is more preferably 126 to 230, and even more preferably 136 to 230. Furthermore, from the viewpoint of crack resistance, the hardness at a depth of 2.2 to 4.4 μm from the surface when measured with a load of 50 g is preferably 110 to 200, and more preferably 120 to 200.

[0108] In the rolled surface treated steel sheet 1 of the present embodiment, from the viewpoint of scratch resistance, the friction coefficient at 4 circumferences in the ball-on-disk friction test is preferably 0.4 or less. On the other hand, the lower limit of the friction coefficient is not particularly limited, but is usually 0.05 or more.

[0109] In addition, from the viewpoint of suppressing the scratching caused by the wear when the roller repeatedly contacts the roller when the sheet is passed, it is preferred that the sum of the friction coefficients at the 0.5-week interval from 0 to 5 weeks (hereinafter also referred to as the sum of the friction coefficients up to 5 weeks) is less than 4.0, more preferably less than 3.5, and further preferably less than 3.1. It should be noted that the lower limit of the sum of the friction coefficients up to 5 weeks is not particularly limited, and is usually 0.3 or more.

[0110] The ball-on-disc friction test is carried out in accordance with JIS R 1613:2010, using a chrome steel ball (SUJ2) with a ball diameter of 6 mm as a contact, under the conditions of a rotation radius of 10 mm, a load of 1.0 N, and a motor speed of 10 rpm. After the test is carried out at 10 revolutions, the sum of the friction coefficients at 4 turns and up to 5 turns can be calculated.

[0111] Next, the thickness of the iron-nickel alloy layer 30 is described. The thickness of the iron-nickel alloy layer 30 contained in the rolled surface-treated steel plate 1 of the present embodiment is preferably 0.4 μm or more, more preferably 0.5 μm or more, and further preferably 0.6 μm or more. There is no particular restriction on the upper limit. If it becomes too thick, the proportion of the hard layer in the rolled surface-treated steel plate 1 increases, and it may be easy to crack. In addition, the resistance increases, so it is preferably 6 μm or less per single side, and more preferably 4 μm or less. In particular, in the case of using a continuous steel strip as the substrate 20, that is, in the case of surface-treating the continuous steel strip to obtain the rolled surface-treated steel plate with an iron-nickel alloy layer of the present embodiment, from the viewpoint of controlling the amount of plating adhesion and avoiding unevenness in heat treatment, the thickness of the iron-nickel alloy layer 30 is preferably 3.5 μm or less, and more preferably 3.0 μm or less.

[0112] The calculation method of the thickness of the iron-nickel alloy layer 30 in this embodiment is described. As the calculation method of the thickness of the iron-nickel alloy layer 30 in this embodiment, it is possible to perform a quantitative analysis of nickel and iron from the surface side to a depth of at least 10 μm in the thickness direction by using SEM-EDX (energy dispersive X-ray spectroscopy) analysis at the cross section of the rolled surface-treated steel plate 1. When the thickness of the iron-nickel alloy layer exceeds 10 μm, a quantitative analysis is performed to the necessary depth.

[0113] An example of a method for obtaining the thickness of the iron-nickel alloy layer 30 from a coordinate graph obtained by SEM-EDX is shown. Figure 4 In the coordinate graph, the horizontal axis represents the distance in the depth direction from the surface layer side (μm), and the vertical axis represents the X-ray intensity of Ni and Fe. Figure 4 In the coordinate diagram of , the shallower part in the thickness direction indicates that the nickel content is high and the iron content is low. On the other hand, the iron content gradually increases as the thickness direction advances.

[0114] In the portion before and after the intersection of the nickel curve and the iron curve, in this embodiment, the distance between 2 / 10 of the maximum values ​​of nickel and iron is defined as the iron-nickel alloy layer 30, and its thickness can be read from the coordinate graph.

[0115] The reason why the distance between 2 / 10 of the respective maximum values ​​of nickel and iron is set as the thickness of the iron-nickel alloy layer 30 in the present embodiment is as follows.

[0116] That is, in the present invention, it is preferred to make the thickness of the iron-nickel alloy layer 30 be above the prescribed value. As a result, it is found that when the thickness of the iron-nickel alloy layer 30 is measured by SEM-EDX, in the sample without heat treatment, that is, in the sample without iron diffusion in nickel, the iron intensity at the position where the nickel intensity becomes the peak is also detected with a value of about 10% to 20% relative to the nickel intensity. In addition, after the nickel intensity decays, that is, in the measurement of the substrate 20 part, with respect to the nickel intensity, a value of about 3 to 8% of the maximum nickel intensity is continuously detected. At this time, the nickel intensity is also about 2% relative to the iron intensity. After decay, even if it is continuously measured for more than 2μm, it will not be less than 1%. That is, it can be known that in the measurement using SEM-EDX, the nickel intensity and the iron intensity are affected by each other in a trace range. Therefore, in this specification, as the thickness of the alloy layer that has become an alloy more reliably, a range of intensities of more than 2 / 10 of each maximum intensity is specified.

[0117] To explain, Figure 1 In the figure, the iron-nickel alloy layer 30 is provided on one side of the substrate 20, but it is not limited thereto, and although not shown, it is preferably provided on both sides of the substrate 20. In addition, when the iron-nickel alloy layer 30 is provided on both sides, the thickness of the iron-nickel alloy layer 30 on one side may be the same thickness as that of the iron-nickel alloy layer 30 on the other side, or may be different thicknesses.

[0118] As a method for forming the iron-nickel alloy layer 30, a method of plating or plating and heat treatment is preferably used. As plating, for example, electroplating, chemical plating, molten plating, dry plating, etc. can be listed. Among them, the method of electroplating is particularly preferred from the perspectives of cost, film thickness control, etc.

[0119] For example, there can be cited a method of forming a nickel plating layer on at least one side of the substrate 20 by electroplating or the like, and then diffusing and alloying the iron (Fe) in the substrate 20 and the nickel (Ni) in the nickel plating layer by thermal diffusion treatment or the like; a method of forming an alloy layer by iron-nickel alloy plating, etc. In particular, in order to control the above-mentioned crystal orientation and grain size and obtain a rolled surface-treated steel sheet with excellent crack resistance and sheet passability, it is preferred to perform nickel plating, and to form an iron-nickel alloy layer by mutually diffusing iron and nickel by thermal treatment to form an iron-nickel alloy layer.

[0120] In the rolled surface-treated steel sheet 1 of the present embodiment, the amount of nickel deposited in the iron-nickel alloy layer 30 is preferably 0.89 g / m 2 ~26.7g / m 2 The amount of nickel deposited in the iron-nickel alloy layer 30 can be measured by fluorescent X-ray analysis (XRF) or the like.

[0121] As a method for measuring the nickel adhesion amount in this embodiment, for example, the method described in International Publication No. WO2020 / 017655 and International Publication No. WO2021 / 020338 can be appropriately adopted. That is, for the rolled surface treated steel plate 1, the total nickel amount can be measured using fluorescent X-ray analysis (XRF) or the like to obtain it.

[0122] The thickness of the entire rolled surface treated steel sheet 1 in the present embodiment will be described. It should be noted that the so-called "thickness of the rolled surface treated steel sheet 1" in the present embodiment may also be measured by cross-sectional observation using a scanning electron microscope (SEM) or by using a micrometer.

[0123] The overall thickness of the rolled surface treated steel sheet 1 in the present embodiment is preferably in the range of 0.03 mm to 0.8 mm. In addition, from the viewpoint of strength and the viewpoint of desired battery capacity, it is more preferably 0.03 mm to 0.3 mm, and when used as a foil that further requires crack resistance and sheet passability, it is more preferably 0.03 mm to 0.15 mm.

[0124] When the thickness exceeds the upper limit of the above-mentioned thickness range or the plate is thick, the surface load (elongation, etc.) for deformation during the plate passing becomes larger, and the surface deformation further increases, which is not preferred. On the other hand, if the thickness is less than the lower limit of the above-mentioned thickness range, the possibility of cracking, breaking, wrinkling, etc. during handling increases. In addition, when used as a battery component, it is sometimes difficult to have sufficient strength for the influence of battery charging and discharging.

[0125] 《Variation Example》

[0126] Explain, if Figure 5As shown in , the present embodiment may be a rolled surface treated steel plate 2 in which a metal layer 40 is formed on an iron-nickel alloy layer 30. It should be noted that the metal layer 40 may be a nickel layer, or a layer composed of other metals other than nickel, for example, a layer composed of zinc, tin, chromium, etc. Zinc and tin may be alloy layers based on them. The layer composed of chromium also includes a chromate layer. The iron-nickel alloy layer 30 of the present embodiment has the characteristics of following the elongation of the substrate and not being easy to crack. Moreover, when the metal layer 40 is formed on the upper layer, the iron-nickel alloy layer that becomes the intermediate layer is not easy to crack, so the crack resistance of the metal layer 40 (such as the nickel layer) of the surface layer also becomes good. As the thickness of the metal layer 40, 0.05 to 3.0 μm is preferred. When a nickel layer is formed as the metal layer 40, the thickness of the upper nickel layer is preferably 0.05 to 0.8 μm, more preferably 0.1 to 0.8 μm, and further preferably 0.15 to 0.7 μm, from the viewpoint of being able to inherit the crystal structure of the lower iron-nickel alloy layer 30 and having good crack resistance. The upper nickel layer can be formed by nickel plating in the steel sheet after rolling the iron-nickel alloy layer.

[0127] In the rolled surface treated steel plate 2, the crystal orientation and the average grain size of nickel are measured in the formed state when the metal layer 40 is a nickel layer or a layer composed of chromium. That is, it is characterized in that while the iron-nickel alloy layer 30 in the rolled surface treated steel plate 2 contains Fe1Ni1, the orientation index in the X-ray diffraction of the (200) plane of Fe1Ni1 is greater than 0.7 and the orientation index in the X-ray diffraction of the (220) plane of Fe1Ni1 is greater than 0.7 and less than 2.5. Furthermore, it is preferred that the difference (absolute value) between the orientation index in the X-ray diffraction of the (200) plane of Fe1Ni1 and the orientation index in the X-ray diffraction of the (220) plane of Fe1Ni1 is less than 1.0. In addition, it is more preferred that the orientation index in the X-ray diffraction of the (111) plane of Fe1Ni1 is 0.3 to 2.0. It should be noted that when the metal layer 40 is a layer composed of zinc or tin, it is preferred to dissolve only the metal layer 40 and then measure.

[0128] For the rolled surface treated steel plate 2 in the present embodiment, when the metal layer 40 is a nickel layer, it is preferred that the average grain diameter of nickel measured by electron beam backscatter diffraction (EBSD) on the surface of the metal layer 40 is 0.4 μm to 1.1 μm. It should be noted that, similarly to the above-mentioned embodiment, the average grain diameter of nickel disclosed in the present invention becomes the average grain diameter of nickel crystals, iron-nickel alloy crystals, or nickel crystals and iron-nickel alloy crystals. That is, in this variant, sometimes, depending on the thickness and concavity of the metal layer 40, the iron-nickel alloy layer 30 is partially exposed on the surface of the rolled surface treated steel plate 2, but the value of the average grain diameter of nickel on the surface of the rolled surface treated steel plate 2 becomes a value reflecting the particle size of both the iron-nickel alloy layer 30 and the metal layer 40. It should be noted that, when the metal layer 40 is a layer composed of zinc or tin, it is preferred to measure only after the metal layer 40 is dissolved.

[0129] In the rolled surface treated steel plate 1 of the present embodiment, it is preferred that its surface is an iron-nickel alloy layer 30, and the proportion of iron on at least the outermost surface is 0 to 65% or less. It should be noted that the proportion of iron on the surface of the above-mentioned rolled surface treated steel foil can be measured by GDS (glow discharge luminescence surface analysis method). In addition, with respect to the rolled surface treated steel plate 2 in the above-mentioned modified example, its surface is a metal layer 40 (for example, a nickel layer). Even in the modified example when the metal layer 40 is a nickel layer, it is preferred that the proportion of iron on at least the outermost surface is 0 to 65% or less. It should be noted that even in the modified example, the above-mentioned iron proportion can be measured by GDS.

[0130] 《Implementation Examples》

[0131] The present invention will be described in more detail below with reference to Examples. First, the measurement methods in the Examples will be described.

[0132] [Measurement and evaluation of cracking (Vickers hardness)]

[0133] The Vickers hardness of the surface layer of the rolled surface treated steel plate was evaluated by measuring it with a hardness tester. A micro Vickers hardness tester (HM-103 manufactured by MITSUYO) was used to measure it in accordance with JIS Z 2244 (Vickers hardness test-test method). As the indenter, two types of loads, 10g and 50g, were used. As a result of the measurement with a load of 10g, the hardness measured at a depth of 0 to 2.2μm was obtained in all embodiments and comparative examples. In addition, as a result of the measurement with a load of 50g, the hardness measured at a depth of 2.2μm to 4.4μm was obtained in all embodiments and comparative examples.

[0134] [Measurement and evaluation of cracking (ease of exposure of iron (Fe) after stress application)]

[0135] The cracking characteristics of the rolled surface treated steel sheet were determined by applying 3% elongation in a tensile test (JIS Z 2241), and then observing the exposure of iron (Fe) from the surface by scanning electron microscope (SEM) and energy dispersive X-ray analysis (EDS). The measurement conditions were as follows.

[0136] Tensile test conditions

[0137] · Sample size: JIS K 6251 standard test piece No. 6

[0138] ·Stretching device: AGX-V manufactured by Shimadzu Corporation

[0139] · Elongation meter: TRViewX manufactured by Shimadzu Corporation

[0140] ·Stretching speed: 1.0 (mm / min)

[0141] Elongation: 1.0%, 3.0%

[0142] ·SEM conditions

[0143] ·Device: VE-8800 manufactured by KEYENCE

[0144] Beam conditions: acceleration voltage 15 kV, irradiation current 5 × 10 -8 A

[0145] Working distance: 35mm

[0146] Observation field: 150μm×150μm

[0147] Observation surface: rolling surface

[0148] Observation magnification: 1000x, 3000x

[0149] EDS conditions

[0150] Device: X-act manufactured by OXFORD

[0151] Analysis method: 10 points (N=10)

[0152] For the sample given an elongation of 3.0% by the tensile test, 10 points where the surface became a concave part were randomly observed in the SEM image, and EDS point analysis was performed at each observation point. For other measurement points, the presence or absence of a clear iron peak height (Fe-rich) part was confirmed, and the number was counted as the confirmation number. If there is an Fe-rich part, it is judged that cracks occur when the elongation is given to 3.0%, and the iron is easily exposed. Preferably, the confirmation position of the Fe-rich part is 6 points or less, and more preferably 3 points or less. Furthermore, in each EDS point analysis, the number of Kα counts of Ni relative to the number of Kα counts of Fe is calculated as a ratio. This ratio is used as the Kα count ratio. The part where the Kα count ratio is less than 3.0 is set as the part other than the Fe-rich part, and the part where the Kα count ratio is the largest is set as the most Fe-rich part. Then, the ratio of the Kα count ratio outside the Fe-rich part to the Kα count ratio of the most Fe-rich part (count number ratio) is calculated to evaluate the exposure degree of the iron component.

[0153] That is, the count quantity ratio in Table 2 is calculated by the following formula.

[0154] Kα count ratio = Kα count number of Fe at the measurement point / Kα count number of Ni at the measurement point

[0155] Count ratio = Kα count ratio of the most Fe-rich site / Kα count ratio of the parts other than the Fe-rich site

[0156] The higher the count ratio, the more exposed the iron is. If the count ratio exceeds 100, it is judged that the iron of the substrate is exposed, if it is 20 or more and 100 or less, it is judged that the iron in the substrate or the iron-nickel alloy layer is exposed, if it is 5 or more and less than 20, it is judged that at least the iron component is exposed, and if it is less than 5, it can be judged that the iron exposure is fully suppressed.

[0157] [Measurement and evaluation of plate penetration (ball-on-disk test)]

[0158] The friction characteristics of the rolled surface treated steel sheet were measured by a ball-on-disc friction test (Tribometer TRB3, manufactured by Anton Paar) to evaluate the passability of the sheet. A chrome steel ball (SUJ2) with a ball diameter of 6 mm was used as a contact, and the rotation radius was set to 10 mm, the load was 1.0 N, the motor speed was 10 rpm, and the number of revolutions was 10. In addition, the friction test was conducted in accordance with JIS R 1613:2010 without lubricant (dry condition).

[0159] The friction coefficient used was the value provided by the software of the tester. In addition, the friction coefficient at 4 weeks where the friction coefficient clearly differed and the sum of the friction coefficient at 0.5 weeks from 0 to 5 weeks were compared to evaluate the passability. The lower the friction coefficient, the less damage to the mold and roller during processing and continuous coating, leading to improved material quality; and the less damage to the equipment (mold, roller), leading to a longer life of the equipment, the evaluation was high in the passability.

[0160] [Measurement and evaluation of hydrogen barrier properties (hydrogen permeation current density)]

[0161] The hydrogen permeation current density is measured using the device described in FIG2 . As a specific method of setting up the sample, as shown in FIG2( a ), two cells, a cell X for hydrogen generation and a cell Y for detecting hydrogen permeation, are prepared, and a test piece (sample) of a rolled surface treated steel plate is set between the two measurement cells. Then, each measurement cell is filled with an electrolyte at 45°C (containing 6 mol / L of KOH as the main component, and an alkaline aqueous solution with a total concentration of KOH, NaOH, and LiOH of 7 mol / L), and the counter electrodes (CE1 and CE2) are immersed. In addition, platinum (Pt) is used as the counter electrode. It should be noted that, as shown in FIG2( b ), the measurement diameter in the rolled surface treated steel plate is set to φ60 mm (measurement area 28.26 cm 2 A rectifier (Kikusui Electronics Co., Ltd., small DC stabilized power supply PMX18-5A) was used for current control on the hydrogen intrusion side, and an ammeter (Hioki Electric Co., Ltd., Digital Marker DT4282) was used for current measurement on the hydrogen detection side.

[0162] As for the specific measurement conditions, 2.25A is applied to the sample on the hydrogen generation side for 30 minutes, hydrogen is generated on the sample surface, and the change in oxidation current generated when hydrogen atoms penetrate on the hydrogen detection side is measured every 10 seconds. It should be noted that no current is applied on the hydrogen detection side. In addition, before the current is applied on the hydrogen generation side, in order to stabilize the surface of the rolled surface treated steel plate, it is immersed in the electrolyte for more than 20 minutes, and the current value of the ammeter on the hydrogen detection side is confirmed to be less than 10μA and becomes stable.

[0163] The hydrogen permeation current density I (μA / cm 2 Specifically, the difference between the oxidation current value when the current was applied for 30 minutes and the current value immediately before the current was applied (0 seconds) was divided by the measurement area of ​​28.26 cm 2 The obtained value was defined as the hydrogen permeation current density. The results are shown in Table 4.

[0164] The hydrogen barrier property was evaluated as follows, and a value of C or higher was determined to be practically suitable.

[0165] A: Hydrogen permeation current density is less than 1.0 μA / cm 2

[0166] B: Hydrogen permeation current density is 1.0μA / cm 2 Above and less than 2.5μA / cm 2

[0167] C: Hydrogen permeation current density is 2.5μA / cm 2 Above and less than 10μA / cm 2

[0168] D: Hydrogen permeation current density is 10μA / cm 2 Above and less than 30μA / cm 2

[0169] E: Hydrogen permeation current density is 30μA / cm 2 above

[0170] [X-ray diffraction (XRD) measurement]

[0171] In order to evaluate the state of the alloy composed of iron and nickel contained in the rolled surface treated steel plate, X-ray diffraction (XRD) measurement was carried out. As an X-ray diffraction measuring device, SmartLab manufactured by Rigaku was used. The sample was cut into 20 mm × 20 mm. As specific measurement conditions for X-ray diffraction, the following specifications were set. The crystal orientation index of the X-ray diffraction of the (200) plane of Fe1Ni1, the crystal orientation index of the X-ray diffraction of the (220) plane of Fe1Ni1, and the crystal orientation index of the X-ray diffraction of the (111) plane of Fe1Ni1 were calculated respectively. In addition, the difference between the crystal orientation index of the (200) plane and the (220) plane was calculated. The results are recorded in Table 5.

[0172] <Device Configuration>

[0173] X-ray source: CuKα

[0174] Goniometer radius: 300nm

[0175] ·Optics: Concentration method

[0176] (Incident side slit system)

[0177] Sunlight slit: 5°

[0178] · Longitudinal limiting slit: 5mm

[0179] Divergence slit: 2 / 3°

[0180] (Light-receiving side slit system)

[0181] Scattering slit: 2 / 3°

[0182] Sunlight slit: 5°

[0183] ·Light receiving slit: 0.3mm

[0184] ·Monochromatization method: Counter monochromator method

[0185] Detector: Scintillation counter <Measurement parameters>

[0186] Target: Cu

[0187] Tube voltage-tube current: 45kV 200mA

[0188] Scanning axis: 2θ / θ (central method)

[0189] Scan mode: continuous

[0190] ·Measurement range: 2θ40~100°

[0191] Scanning speed: 10° / min

[0192] Step: 0.02°

[0193] [Method for calculating the average particle size from electron beam backscatter diffraction (EBSD) measurement data]

[0194] In the obtained rolled surface treated steel sheet, a crystal orientation analysis using EBSD (electron back scattering diffraction) was performed using a scanning electron microscope (SEM), thereby obtaining the nickel grain size. Specifically, the information of the diffraction pattern called the Kikuchi pattern was obtained and analyzed under the following conditions, thereby obtaining the average grain size. Specifically, the value calculated as the Average Number (Diameter) was obtained as the average grain size.

[0195] It is explained that when measuring, the diffraction pattern of nickel is specified, but the information is obtained in the same diffraction pattern by the iron-nickel alloy having a face-centered cubic crystal structure close to nickel, so the average crystal grain diameter of the nickel using EBSD measurement data in the present invention becomes the average crystal grain diameter of the crystal of nickel, the crystal of the iron-nickel alloy, or the crystal of nickel and the crystal of the iron-nickel alloy. The average crystal grain diameter obtained is shown in Table 6.

[0196] <EBSD measurement conditions and analysis conditions>

[0197] ·SEM: SU8020 manufactured by Hitachi High-Tech

[0198] ·Measurement procedure: OIMDataCollect ion

[0199] Data analysis program: OIMAnalys is (Ver.6.2.0)

[0200] ·Measurement range: 100μm×120μm

[0201] Grain Tolerance Angle: 5°

[0202] Step width: 0.20μm

[0203] Average (diameter)

[0204] <Example 1>

[0205] First, as a substrate, a cold-rolled foil (thickness 55 μm) of low-carbon aluminum-killed steel having the chemical composition shown below was prepared.

[0206] C: 0.04 wt%, Mn: 0.32 wt%, Si: 0.01 wt%, P: 0.012 wt%, S: 0.014 wt%, balance: Fe and inevitable impurities

[0207] Next, the prepared substrate was subjected to electrolytic degreasing and pickling by immersion in sulfuric acid, and then nickel-plated on both sides of the steel foil under the following conditions to form a 0.5 μm thick nickel-plated layer on both sides. The nickel-plating conditions were as follows.

[0208] (Nickel plating conditions)

[0209] Bath composition:

[0210] Nickel sulfate hexahydrate: 250g / L

[0211] Nickel chloride hexahydrate: 45g / L

[0212] Boric acid: 30g / L

[0213] Bath temperature: 60°C

[0214] pH: 4.0~5.0

[0215] Stirring: air stirring or jet stirring

[0216] Current density: 10A / dm 2

[0217] Next, for the steel foil having the nickel-plated layer formed as described above, heat treatment (heat treatment process) is performed by box annealing under the conditions of a soaking temperature of 560°C, a soaking time of 6 hours, and a reducing atmosphere. By this heat treatment, a nickel-plated surface-treated steel plate having an iron-nickel alloy layer on both sides is obtained. Next, rolling (rolling process) is performed for the nickel-plated surface-treated steel plate. As rolling conditions, cold rolling with a reduction rate of 11% is used. It is to be noted that the reduction rate is a calculated value when the thickness of the nickel-plated steel plate before rolling (the thickness of the substrate and the thickness of the nickel-plated layer on both sides) is 50 μm by rolling. For the rolled surface-treated steel plate (nickel-plated surface-treated steel plate after the rolling process) thus obtained, cracking (hardness and Fe exposure after being given by tensile elongation) evaluation, plate passability (friction coefficient) evaluation, hydrogen barrier evaluation, X-ray diffraction measurement, and average particle size calculation are performed.

[0218] <Example 2>

[0219] The same procedure as in Example 1 was performed except that the thickness of the nickel plating layers on both surfaces by nickel plating was 1.0 μm and the reduction ratio in the rolling step was 12%.

[0220] <Example 3>

[0221] The same procedure as in Example 1 was carried out except that the soaking temperature in the heat treatment step was 590°C.

[0222] <Example 4>

[0223] The same procedure as in Example 2 was performed except that the thickness of the nickel plating layers on both surfaces by nickel plating was 1.0 μm, the soaking temperature in the heat treatment step was 590° C., and the reduction ratio in the rolling step was 12%.

[0224] <Example 5>

[0225] The same procedure as in Example 3 was performed except that the thickness of the substrate was 60 μm, the soaking temperature in the heat treatment step was 590° C., and the reduction ratio in the rolling step was 18%.

[0226] <Example 6>

[0227] The same procedure as in Example 5 was performed except that the thickness of the nickel plating layers on both surfaces by nickel plating was 0.4 μm, the soaking temperature in the heat treatment step was 560° C., and the reduction ratio in the rolling step was 18%.

[0228] <Example 7>

[0229] The same procedure as in Example 6 was carried out except that the thickness of the nickel-plated layers on both surfaces by nickel plating was set to 0.2 μm.

[0230] <Example 8>

[0231] The same procedure as in Example 6 was carried out except that the thickness of the nickel-plated layers on both surfaces by nickel plating was set to 0.18 μm.

[0232] <Example 9>

[0233] The same procedure as in Example 5 was carried out except that the thickness of the nickel-plated layers on both surfaces by nickel plating was set to 0.2 μm.

[0234] <Example 10>

[0235] The same procedure as in Example 6 was carried out except that the thickness of the nickel-plated layers on both surfaces by nickel plating was set to 0.1 μm.

[0236] <Example 11>

[0237] After the rolling process, impact nickel plating and a second nickel plating are further performed to form a nickel layer on the iron-nickel alloy layer. Otherwise, the same method as in Example 8 is used. The second nickel plating is performed under the same plating conditions as when the substrate is subjected to the nickel plating. The thickness of the nickel layer on the iron-nickel alloy layer after the second nickel plating is 0.5 μm. Each evaluation is performed using the rolled surface treated steel sheet after the nickel layer is formed.

[0238] <Comparative Example 1>

[0239] The thickness of the substrate was set to 50 μm, and the thickness of the nickel-plated layers on both surfaces by nickel plating was set to 0.35 μm, and no heat treatment or rolling was performed.

[0240] <Comparative Example 2>

[0241] The thickness of the substrate was set to 200 μm, and the thickness of the nickel plating layer on both sides produced by nickel plating was set to 0.4 μm on one side and 1.0 μm on the other side. In addition, the heat treatment temperature in the heat treatment step was set to 800° C., and the heat treatment time was 1 minute for continuous annealing, and no rolling was performed. Other than this, the same procedure as in Example 1 was followed.

[0242] <Comparative Example 3>

[0243] The thickness of the substrate was set to 200 μm, and the thickness of the nickel plating layer on both sides produced by nickel plating was set to 3.0 μm on one side and 1.0 μm on the other side. In addition, the heat treatment temperature in the heat treatment step was set to 800° C., and the heat treatment time was 1 minute of continuous annealing, and no rolling was performed. Other than this, the same procedure as in Example 1 was followed.

[0244] <Comparative Example 4>

[0245] The thickness of the substrate was set to 200 μm, and the thickness of the nickel-plated layers on both sides produced by nickel plating was set to 5.0 μm. In addition, the heat treatment temperature in the heat treatment process was set to 670°C, and the heat treatment was performed continuously for 40 seconds. The reduction ratio in the rolling process was the initial reduction ratio after the nickel plating process, which was 65-75%. Other than this, the same process as in Example 1 was performed.

[0246] <Comparative Example 5>

[0247] The same procedure as in Comparative Example 4 was performed except that after rolling at a reduction ratio of 65 to 75%, heat treatment was performed at 590° C. for 6 hours by box annealing, and cold rolling was performed at a reduction ratio of 15 to 20%.

[0248] The thickness of the substrate and the conditions of each step are shown in Table 1. In addition, each measurement value and evaluation result are shown in Table 2 and thereafter.

[0249] [Table 1]

[0250]

[0251] [Table 2]

[0252]

[0253] ※Value after stretching 1%

[0254] [Table 3]

[0255]

[0256] [Table 4]

[0257]

[0258] [Table 5]

[0259]

[0260] [Table 6]

[0261]

[0262] According to Examples and Comparative Examples, the rolled surface-treated steel sheet in the present embodiment can be evaluated as follows.

[0263] Regarding cracking property, it can be said that a hard film such as nickel is easy to crack in general. On the other hand, the results of comparing Examples 1 to 11 with Comparative Example 1 show that the rolled surface treated steel sheets of the Examples have good properties of being difficult to crack, since the exposure of iron is difficult to occur even when stress such as tensile stress is applied, while maintaining the hardness at the same level as the nickel-plated steel sheet of Comparative Example 1.

[0264] In addition, the results of comparing Examples 1 to 11 and Comparative Examples 2 to 3 show that the rolled surface-treated steel plates of the examples maintain a higher hardness than the nickel-plated steel plates of the comparative examples, and even when stress such as stretching is applied, iron exposure is unlikely to occur, and the plates have the good property of being difficult to crack.

[0265] Furthermore, the results of comparing Examples 1 to 11 and Comparative Example 4 can be evaluated as follows: Comparative Example 4, which was rolled at a high reduction rate, broke before 3% elongation was applied, and even at 1% elongation, there were many areas where iron was exposed, but the rolled surface-treated steel plate of the embodiment had a good characteristic of being difficult to crack even with an additional 3% elongation.

[0266] Furthermore, the results of comparing Examples 1 to 11 and Comparative Example 5 can be evaluated as follows: for Comparative Example 5, which was rolled at a high reduction rate and then subjected to a second heat treatment and a second rolling, the hardness became equivalent to that of Comparative Example 1, and the iron exposure after 3% stretching was also improved. On the other hand, the rolled surface-treated steel plates of the embodiments had better characteristics than those of the embodiments in terms of cracking resistance.

[0267] Regarding the passability, the results of comparing the embodiment and the comparative example show that the rolled surface treated steel plate of the embodiment has a significantly lower friction coefficient than the nickel-plated steel plate of the comparative example. Specifically, the friction coefficient of 4 weeks is excellent, which is less than 0.4. In addition, the sum of 0 to 5 weeks is also significantly lower than that of the comparative example. As a result, a good surface with less scratches caused by wear can be made, and scratches caused by wear when the roller passes the plate can be suppressed. In particular, the scratch resistance is excellent when the drawing roller passes the plate, when the feed roller passes the plate sequentially, and when applying another layer such as an active material to the upper layer.

[0268] As for the hydrogen barrier property, the results of comparison between the Examples and the Comparative Examples show that the rolled surface-treated steel sheets of the Examples have hydrogen barrier properties equal to or higher than those of the nickel-plated steel sheets and the surface-treated steel sheets of the Comparative Examples.

[0269] Regarding the orientation index, the results of comparing the examples and comparative examples show that the rolled surface treated steel sheet of the example can be made into a layer that is difficult to crack while maintaining appropriate hardness by orienting the Fe1Ni1 grains in the iron-nickel alloy layer in a state where both (200) and (220) are moderately mixed. In addition, it is believed that the hydrogen barrier property is excellent and the increase in the friction coefficient can be suppressed. On the other hand, for Comparative Examples 4 and 5, since they have undergone a rolling process under a high reduction rate, they are oriented predominantly in (220).

[0270] Regarding the average grain size, the results of comparing the examples and comparative examples confirmed that the Ni-based fcc grain size of the rolled surface treated steel sheet of the examples was larger than that of the nickel-plated steel sheet of Comparative Example 1. Based on the examples of the present invention, it is believed that the increase in the friction coefficient can be suppressed by making the average grain size 0.4 μm or more.

[0271] In addition, when comparing Comparative Example 3, which was heat-treated after nickel plating, with Examples 1 to 11, it was confirmed that the grains of Comparative Example 3 were coarsened by heat treatment, and the average grain diameter became larger. In addition, it can be understood that in Comparative Example 3, since the average grain diameter is large and soft, shear deformation occurs due to the shear stress during friction, so the friction coefficient increases. On the other hand, it is believed that in the examples, the increase in the friction coefficient can be suppressed by making the average grain diameter 0.4μm to 1.1μm. In addition, it is believed that the hardness of the outermost surface of the rolled surface-treated steel plate and the intermediate layer between the substrate and the outermost surface can be within an appropriate range.

[0272] In addition, if the comparative example 5 in which the iron-nickel alloy layer is formed and rolled at a high reduction rate is compared with the examples 1 to 11, it is confirmed that, in the comparative example 5, the grains are coarsened and become larger by the rolling and heat treatment at a high reduction rate. On the other hand, it is believed that, in the examples, the increase in the friction coefficient can be suppressed by making the average grain diameter 0.4 μm to 1.1 μm. In addition, it is believed that the hardness of the outermost surface of the rolled surface-treated steel plate and the intermediate layer between the substrate and the outermost surface can be within an appropriate range.

[0273] The above-mentioned embodiments and examples can be variously modified without departing from the scope of the present invention. In addition, the rolled surface treated steel sheet in the above-mentioned embodiments and examples is mainly described as a rolled surface treated steel sheet for a collector for a secondary battery, but is not limited thereto and can also be suitable for use in small electronic devices, etc.

[0274] Industrial Applicability

[0275] As described above, the rolled surface-treated steel sheet of the present invention can be applied to battery components such as current collectors, battery containers, and terminals of various batteries, electronic related devices, and the like.

[0276] Description of Reference Numerals

[0277] 1: Rolled surface treated steel plate

[0278] 20: Base material

[0279] 30: Iron-nickel alloy layer

[0280] 2: Rolled surface treated steel plate

[0281] 40: Metal layer

Claims

1. A method for manufacturing a rolled surface-treated steel plate, comprising: An iron-nickel alloy layer forming step of forming an iron-nickel alloy layer on a steel plate as a substrate; and A rolling step of rolling the steel sheet having the iron-nickel alloy layer at a reduction ratio of 5 to 25% is performed after the iron-nickel alloy layer forming step.

2. The method for producing a rolled surface-treated steel sheet according to claim 1, wherein: The iron-nickel alloy layer forming process comprises: A nickel plating step of forming a nickel plating layer on the steel plate as the substrate; and A heat treatment step of heat-treating the nickel-plated material obtained in the nickel plating step to form the iron-nickel alloy layer produced by diffusion.

3. A rolled surface treated steel plate, characterized in that: The invention comprises: a substrate composed of steel, and an iron-nickel alloy layer provided on the substrate. The iron-nickel alloy layer contains Fe1Ni1, and the orientation index of the (200) plane of Fe1Ni1 in X-ray diffraction is greater than 0.7, and the orientation index of the (220) plane of Fe1Ni1 in X-ray diffraction is greater than 0.7 and less than 2.

5.

4. The rolled surface-treated steel plate according to claim 3, wherein: The average crystal grain size of nickel measured by EBSD on the surface of the rolled surface-treated steel sheet was 0.4 μm to 1.1 μm.

5. The rolled surface-treated steel plate according to claim 3, wherein: The difference (absolute value) between the orientation index in X-ray diffraction of the (200) plane of the Fe1Ni1 and the orientation index in X-ray diffraction of the (220) plane of the Fe1Ni1 is 1.0 or less.

6. The rolled surface-treated steel plate according to claim 3, wherein: The orientation index of the (111) plane of the Fe1Ni1 in X-ray diffraction is 0.3 to 2.0.

Citation Information

Patent Citations

  • Method of determining reliability of power supply systems

    SU570058A1

  • Steel foil and method for producing same

    WO2013157600A1

  • Roughened nickel-plated sheet

    WO2020017655A1

  • Roughened nickel-plated material and method for producing same

    WO2021020338A1